1996
DOI: 10.1111/j.1432-1033.1996.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced B Subunit of Heat‐Labile Enterotoxin Associates with Membranes In vivo

Abstract: The B subunit of heat-labile enterotoxin, a periplasmic protein of Escherichia coli has an internal disulfide bond that forms after the protein has been exported. The presence of 2.5 mM dithiothreitol in the medium prevents the formation of the disulfide bond and this causes the protein to rapidly bind to membranes, preferentially but not exclusively to the cytoplasmic membrane. The binding is irreversible in vivo but chaotropic agents disrupt the association between the non-native B subunit and the membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…The A2 fragment ends in a somewhat disordered segment adopting a small helix, where the pore is widening toward the membrane (Figure 7.2A, insert). This segment is more buried in CT compared to LT, where it extends further through the pore (Figure 7.3), potentially explaining the milder symptoms caused by LT compared to CT [27]: A larger number of interactions of the B pentamer with the CTA2 tail compared to LTA2 rationalizes the increased stability and concomitant increase in toxicity observed for holotoxin chimera featuring the 10-amino-acid-residue-stretch from CT (226)(227)(228)(229)(230)(231)(232)(233)(234)(235)(236) [40,41], since holotoxin integrity is important during uptake and transport into intestinal epithelia. At the very tip of the A2 fragment, pointing toward the membrane, is a stretch of highly disordered amino acids with the KDEL-sequence (-Lys-Asp-Glu-Leu-COOH) (LT: RDEL, with Arg replacing Lys), aiding the transport of the toxin to the endoplasmic reticulum (ER) after internalization.…”
Section: A Subunitmentioning
confidence: 95%
See 2 more Smart Citations
“…The A2 fragment ends in a somewhat disordered segment adopting a small helix, where the pore is widening toward the membrane (Figure 7.2A, insert). This segment is more buried in CT compared to LT, where it extends further through the pore (Figure 7.3), potentially explaining the milder symptoms caused by LT compared to CT [27]: A larger number of interactions of the B pentamer with the CTA2 tail compared to LTA2 rationalizes the increased stability and concomitant increase in toxicity observed for holotoxin chimera featuring the 10-amino-acid-residue-stretch from CT (226)(227)(228)(229)(230)(231)(232)(233)(234)(235)(236) [40,41], since holotoxin integrity is important during uptake and transport into intestinal epithelia. At the very tip of the A2 fragment, pointing toward the membrane, is a stretch of highly disordered amino acids with the KDEL-sequence (-Lys-Asp-Glu-Leu-COOH) (LT: RDEL, with Arg replacing Lys), aiding the transport of the toxin to the endoplasmic reticulum (ER) after internalization.…”
Section: A Subunitmentioning
confidence: 95%
“…TF, Trigger factor. are further known to catalyze disulfide bond formation in both toxin A (Cys187-Cys199) and B (Cys9-Cys86) subunits, which is required for their functional assembly [53,230,234,236,237]. In addition, a cis-proline at position 93 in the B subunits is necessary for efficient B pentamer formation [32].…”
Section: Toxin Folding and Assemblymentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously found that when the formation of the internal disulfide bond in the B subunit of heat-labile enterotoxin is prevented by the presence of dithiothreitol (DTT) in the medium, the protein is exported through the cytoplasmic membrane, but binds to the available membranes in the periplasm, instead of remaining soluble and assembling into a pentamer [4]. This conclusion was based on experiments in which B subunit synthesised in the presence of DTT sedimented quantitatively with membranes, floated quantitatively with membranes, and was distributed across both the cytoplasmic and outer membrane peaks after equilibrium sucrose density gradient centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…The B subunit of heat-labile enterotoxin is a highly charged monomer and yet forms a tight association with membranes if unable to assemble into pentamers [4,6]. The association occurs whether the B subunit is a wild-type monomer prevented from forming its internal disulfide bond, or a mutant monomer or dimer.…”
Section: ---mentioning
confidence: 99%